Retraction notice to “Pore size variation of nanoporous fixer on the engine bowl and its combined effects on hybrid nano-fuelled CI engine characteristics” [Fuel 345 (2023) 128149] - T. Sathish; Ümit Ağbulut; K. Muthukumar; R. Saravanan; Mamdooh Alwetaishi; Saboor Shaik; C.Ahamed Saleel (Fuel, 2026)

Evolutionary and Structural Insights into Proline Metabolism Genes Associated with Salt Resilience in Mango - Laxmi Rastogi; Anju Bajpai; Sumit K. Soni; M. Muthukumar (Biochemical Genetics, 2026)

Salinity and nutrient driven shifts in diatom dominance along the Tamil Nadu coast during the northeast monsoon - M.D. Bharathi; C. Muthukumar; B. Charan Kumar; Deviram Garlapati; Sivaji Patra; K. Ramu; M.V. Ramana Murthy; R.S. Kankara (Marine Pollution Bulletin, 2026)

Valorization of biomacromolecular algae oil via nanoparticle-enriched blends for eco-friendly fuel performance - Ali El-Rayyes; Hassen Sabeur; S. Dhivya; K. Muthukumar; Muneera Altayeb; Ankur Bahl; A.Anderson (Fuel, 2026)

Impact of Noctiluca scintillans bloom and decay phases on coastal water quality and zooplankton dynamics in Indian coastal waters - Rengasamy Subramaniyan Sathishkumar; Anjusha Arayillath; Sankar Ganesh Ramakrishnan; Muthukumar Chandrasekaran; Chinmay Shah; Logesh Natarajan; Sanitha K. Sivadas; Karri Ramu (Frontiers in Marine Science, 2026)
Introduction Understanding of ecosystem changes induced by harmful algal blooms (HABs) and their impacts on coastal water quality, bacteria, and zooplankton communities remains limited. Non-toxic HABs, particularly Noctiluca scintillans , are increasingly reported in Indian coastal waters. Methods In the present study, a greenish bloom of N. scintillans was observed along the Gulf of Mannar and the Southeastern Arabian Sea during November 2022, with a consequent bloom crash (evidencing surface foam) observed along the southern Kerala coast. We collected samples from bloom, decay, and non-bloom zones to assess changes in hydrobiological conditions. Results and discussion Physicochemical data showed negligible variations in temperature (28.71–29.66 °C) and salinity (34.6–35.06), whereas dissolved oxygen levels varied from 6.06 to 8.47 mg/L. Nutrients exhibited strong fluctuations, particularly with the ammonium concentration (15.80 μmol/L) being higher during the bloom decay phase. Elevated chlorophyll-a and DOC confirmed high biomass and organic release, while bacterial pathogens proliferated under nutrient-rich conditions. Moreover, the concurrent rise in pathogenic bacteria, including Vibrio cholerae , suggests N. scintillans may serve as a potential vector for bacterial proliferation when it forms blooms. Zooplankton assemblages showed distinct responses during the bloom and decay phases of N. scintillans . Micro- and meso-zooplankton densities were elevated during the bloom. In contrast, the mesozooplankton was primarily dominated by calanoid copepods; later, these dominant taxa declined sharply during the decay phase and was substituted by cladocerans, appendicularians, and hydrozoans. These shifts in zooplankton communities reflect changes in hydrographic conditions associated with eutrophication and enhanced bacterial production during bloom collapse.

A critical review on technical advances and multifaceted role of carotenoids in human health with special emphasis on metabolic diseases - Sayani Roy; K. C. Dora; Siddhnath Kumar; Pooja Saklani; A. Muthukumar; Fatih Ozogul; K. C. Harisankar; R. D. Mutum; S. Celine Hilda Mary; V. K. R. Surasani; P. K. Dara (Phytochemistry Reviews, 2026)

Molecular Dissection of Constans (CO) Homologs and Their Regulatory Role in Floral Induction of Mango (Mangifera indica L.) - M. Muthukumar; Anju Bajpai; Kasim Khan; Yashi Bajpai; Sandeep Kumar; Sumit Kumar Soni; Laxmi; V. K. Singh; T. Damodaran (Applied Fruit Science, 2025)

Peptide Epitope-Based Avian IgY Antibodies against SARS-CoV-2 Spike: A Cost Effective Approach for Viral Detection and Neutralization - G. N. Pramod; Prasan Havlad; Nalina Murthy; Abdul Majid; Jessie Thomas; M. Ghalib Enayathullah; Yogesh Sardana; P. K. Sreeram; S. P. Muthukumar; Tanaji Kudre; Pananghat Gayathri; Kiran Kumar Bokara; et al. (International Journal of Peptide Research and Therapeutics, 2025)

Identifying the causal agent of floral malformation as Fusarium complex using metagenomic and metabolomic approaches - M. Muthukumar; Anju Bajpai; Sumit K. Soni; Sanjay Kumar Singh; Yashi Bajpai; Sandeep Kumar; Laxmi (Physiological and Molecular Plant Pathology, 2025)

High Resolution Sentinel-2 and Sentinel-3 Satellite Imagery in Monitoring Green Noctiluca scintillans Blooms in Complex Coastal Waters: A Case Study in Gulf of Mannar - Logesh Natarajan; Muthukumar Chandrasekaran; Manigandan Vajravelu; Chinmay Shah; Sanitha K. Sivadas; Karri Ramu; M. V. Ramana Murthy (Journal of the Indian Society of Remote Sensing, 2025)

Recurrent Swarms of Planktonic Shrimp Luciferidae De Haan, 1849 (Order: Decapoda) in the Neritic Waters of Tamil Nadu, Southeast Coast of India - R. S. Sathishkumar; B. Charan Kumar; C. Muthukumar; N. Logesh; Sanitha K. Sivadas; K. Ramu; M. V. Ramana Murthy (Marine Ecology, 2024)
Luciferidae (Decapoda) are an important component of mesozooplankton in pelagic food webs. This study investigated the spatiotemporal distribution and frequency of Luciferidae swarms along the Tamil Nadu coast, as observed during coastal monitoring cruises conducted between 2019 and 2022. Data were collected on various hydrobiological factors, including surface water temperature, salinity, chlorophyll a , zooplankton biomass, and the abundance of other mesozooplankton (such as copepods, cladocerans, and others) across eight locations in the coastal waters of Tamil Nadu, India. Salinity values were generally low ( Belzebub hanseni Nobili, 1905, as the only organism responsible for swarm formation, with its occurrence peaking in January 2022. During this period, B. hanseni reached a maximum abundance of 3294 ind. m −3 for adults and 4056 ind. m −3 for larvae, together contributing approximately 27% of the total zooplankton abundance. Swarms of B. hanseni were observed a total of seven times over the course of the study, correlating with periods of low sea surface temperature and high food availability. Pearson's correlation analysis revealed a significant relationship between the abundance of copepods and B. hanseni ( r = 0.84; p B. hanseni in the nearshore waters of the Tamil Nadu coast is largely driven by food availability and optimal environmental conditions, including water temperature and monsoonal influences. The findings also suggest that geographical features, such as mangrove habitats, may contribute to the occurrence of B. hanseni swarms in this region.

Downcycled neat LDPE plastic wastes fuelled CI engine’s carbon and soot emission reduction with an elevated performance by Acetylene (HC CH) premixed combustion - K. Muthukumar; G. Kasiraman (Process Safety and Environmental Protection, 2024)

Phylogenetic affiliation of Pedinomonas noctilucae and green Noctiluca scintillans nutritional dynamics in the Gulf of Mannar, Southeastern Arabian Sea - Vajravelu Manigandan; Chandrasekaran Muthukumar; Chinmay Shah; Natarajan Logesh; Sanitha K. Sivadas; Karri Ramu; M.V. Ramana Murthy (Protist, 2024)

Evaluation of groundwater for nitrate and fluoride in Alappuzha region from the southwestern coast of India and associated health risks - S. Selvam; Akhila V. Nath; Priyadarsi D. Roy; K. Jesuraja; P. Muthukumar (Environmental Research, 2023)

First report on the occurrence of Gonyaulax polygramma bloom during the onset of Noctiluca scintillans bloom along the Tuticorin coast, southeast coast of India - M.D. Bharathi; C. Muthukumar; R.S. Sathishkumar; K. Ramu; M.V. Ramana Murthy (Marine Pollution Bulletin, 2023)

Distribution and diversity of Fusarium oxysporum f.sp. cubense TR4 causing banana wilt in Sub-tropics of India and comparative analysis of TR4 specific molecular detection methods - Nidhi Kumari; Thukkaram Damodaran; Israr Ahmad; Shailendra Rajan; P. K. Shukla; Muthukumar Manoharan; Amar Kant Kushwaha; Haripal Singh; Ram Gopal; Sangeeta Kumari; Kavita Yadav; Popy Bora; et al. (Journal of Plant Biochemistry and Biotechnology, 2023)

RETRACTED: Pore size variation of nano-porous material fixer on the engine bowl and its combined effects on hybrid nano-fuelled CI engine characteristics - T. Sathish; Ümit Ağbulut; K. Muthukumar; R. Saravanan; Mamdooh Alwetaishi; Saboor Shaik; C. Ahamed Saleel (Fuel, 2023)

A novel investigations on medical and non-medical mask performance with influence of marine waste microplastics (polypropylene) - T. Sathish; R. Saravanan; Kamal Sharma; Sasan Zahmatkesh; K. Muthukumar; Hitesh Panchal (Marine Pollution Bulletin, 2023)

Downcycling of one-time used plastic waste to DICI engine combustion energy through pyrolysis with less NOx emission - K. Muthukumar; G. Kasiraman (Process Safety and Environmental Protection, 2023)

An absorber of parabolic trough collector for hydrogen production in a solid oxide fuel cell - T. Sathish; C. Sailaja; R. Saravanan; Pelluru Suresh; M. Anish; M. Rajasimman; Usha Sambath; N. Sabarirajan; K. Muthukumar; Sang-Woo Joo; Yasser Vasseghian (Fuel, 2023)

Strain Identification and Herbivore–Host Interaction of Maize Hosting Invasive Alien Pest Spodoptera frugiperda under Elevated Temperature and CO2 Levels - K. Ashok; V. Balasubramani; M. Muthukumar; J. S. Kennedy; V. Geethalakshmi; N. Sathiah (Agricultural Research, 2023)

Enhanced waste cooking oil biodiesel with Al2O3 and MWCNT for CI engines - T. Sathish; K. Muthukumar; AbdulKareem Abdulwahab; M. Rajasimman; R. Saravanan; K. Balasankar (Fuel, 2023)

Therapeutic Potential of Semaglutide, a Newer GLP-1 Receptor Agonist, in Abating Obesity, Non-Alcoholic Steatohepatitis and Neurodegenerative diseases: A Narrative Review - Manoj K. Mahapatra; Muthukumar Karuppasamy; Biswa M. Sahoo (Pharmaceutical Research, 2022)

Sustenance of Indian Moored Buoy Network During COVID-19 Pandemic – A Saga of Perseverance - R. Venkatesan; K. Jossia Joseph; C. Anoopa Prasad; M. Kalyani; M. Arul Muthiah; S. Ramasundaram; P. Murugesh; K. Thirumurugan; R. Sundar; B. Kesavakumar; G. Vengatesan; K. Ramesh; et al. (Frontiers in Marine Science, 2021)
The moored buoy network in the Indian Ocean revolutionized the observational programs with systematic time-series measurement of in situ data sets from remote marine locations. The real-time meteorological and oceanographic data sets significantly improved the weather forecast and warning services particularly during extreme events since its inception in 1997. The sustenance of the network requires persistent efforts to overcome the multitude of challenges such as vandalism, biofouling, rough weather, corrosion, ship time availability, and telemetry issues, among others. Besides these, the COVID-19 pandemic constrained the normal functioning of activities, mainly by delaying the maintenance of the network that resulted in losing a few expensive buoy system components and precious data sets. However, the improvements in the buoy system, in-house developed data acquisition system, and efforts in ensuring the quality of measurements together with “best practice methods” enabled 73% of the buoy network to be functional even when the cruises were reduced to 33% during the COVID-19 lockdown in 2020. The moored buoys equipped with an Indian buoy data acquisition system triggered high-frequency transmission during the Super cyclone Amphan in May 2020, which greatly helped the cyclone early warning services during the COVID-19 pandemic. The COVID-19 lockdown points toward the reliability and enhanced utility of moored buoy observations particularly when other modes of measurements are limited and necessitates more such platforms to better predict the weather systems. The present study analyzed the enhancement of the buoy program and improvisation of the buoy system that extended the life beyond the stipulated duration and enabled the high-frequency data transmission during cyclones amid the COVID-19 lockdown. The recommendations to better manage the remote platforms specifically in the event of a pandemic based on the operational experience of more than two decades were also presented.

Geomorphology and Landslide Proneness of Kerala, India A Geospatial study - SM. Ramasamy; S. Gunasekaran; J. Saravanavel; R. Melwyn Joshua; R. Rajaperumal; R. Kathiravan; K. Palanivel; M. Muthukumar (Landslides, 2021)

Socio-ecological studies on a tropical coastal area in southern India - M. S. Gokul; H.-U. Dahms; S. Henciya; T. Dhineshkumar; K. Muthukumar; R. A. James (International Journal of Environmental Science and Technology, 2019)

First report on wilt disease of mango caused by Ceratocystis fimbriata in Uttar Pradesh, India - P. K. Shukla; Savita Varma; Tahseen Fatima; Anju Bajpai; Rupesh Mishra; A. K. Misra; Gundappa; M. Muthukumar (Indian Phytopathology, 2018)

Global asymptotic stability of complex-valued neural networks with additive time-varying delays - K. Subramanian; P. Muthukumar (Cognitive Neurodynamics, 2017)

Characterisation of defatted Scenedesmus dimorphus algal biomass as animal feed - S. Vidyashankar; K. S. VenuGopal; V. S. Chauhan; S. P. Muthukumar; R. Sarada (Journal of Applied Phycology, 2015)

Optimization of aqueous methylparathion biodegradation by Fusarium sp in batch scale process using response surface methodology - K. Usharani; M. Muthukumar (International Journal of Environmental Science and Technology, 2013)

Introgression of bacterial leaf blight resistance and aroma genes using functional marker-assisted selection in rice (Oryza sativa L.) - R. K. Salgotra; B. B. Gupta; Reginald J. Millwood; Muthukumar Balasubramaniam; C. N. Stewart (Euphytica, 2012)

Optimization of Antimicrobial Production by a Marine Actinomycete Streptomyces afghaniensis VPTS3-1 Isolated from Palk Strait, East Coast of India - R. Vijayakumar; K. Panneerselvam; C. Muthukumar; N. Thajuddin; A. Panneerselvam; R. Saravanamuthu (Indian Journal of Microbiology, 2012)

Optimization of electro-oxidation process for the treatment of Reactive Orange 107 using response surface methodology - K. Rajkumar; Muthuchamy Muthukumar (Environmental Science and Pollution Research, 2012)

Arbuscular mycorrhizal morphology and dark septate fungal associations in medicinal and aromatic plants of Western Ghats, Southern India - T. Muthukumar; M. Senthilkumar; M. Rajangam; K. Udaiyan (Mycorrhiza, 2006)

Growth of Nursery-grown Bamboo Inoculated with Arbuscular Mycorrhizal Fungi and Plant Growth Promoting Rhizobacteria in two Tropical Soil Typeswith and without Fertilizer Application - T. Muthukumar; K. Udaiyan (New Forests, 2006)

Mycorrhiza in sedges?an overview - T. Muthukumar; K. Udaiyan; P. Shanmughavel (Mycorrhiza, 2004)

Response of neem (Azadirachta indica A. Juss) to indigenous arbuscular mycorrhizal fungi, phosphate-solubilizing and asymbiotic nitrogen-fixing bacteria under tropical nursery conditions - T. Muthukumar; K. Udaiyan; V. Rajeshkannan (Biology and Fertility of Soils, 2001)

Influence of organic manures on arbuscular mycorrhizal fungi associated with Vigna unguiculata (L.) Walp. in relation to tissue nutrients and soluble carbohydrate in roots under field conditions - T. Muthukumar; K. Udaiyan (Biology and Fertility of Soils, 2000)

The role of seed reserves in arbuscular mycorrhizal formation and growth of Leucaena leucocephala (Lam.) de Wit. and Zea mays L. - T. Muthukumar; K. Udaiyan (Mycorrhiza, 2000)

Arbuscular mycorrhizas of plants growing in the Western Ghats region, Southern India - T. Muthukumar; K. Udaiyan (Mycorrhiza, 2000)